Evidence that conflict regarding size of haemodynamic response to interventricular delay optimization of cardiac resynchronization therapy may arise from differences in how atrioventricular delay is kept constant. Issue 12 (8th April 2015) - Sohaib, S.M. Afzal; Kyriacou, Andreas; Jones, Siana; Manisty, Charlotte H.; Mayet, Jamil; Kanagaratnam, Prapa; Peters, Nicholas S.; Hughes, Alun D.; Whinnett, Zachary I.; Francis, Darrel P.
Abstract : Aims: Whether adjusting interventricular (VV) delay changes haemodynamic efficacy of cardiac resynchronization therapy (CRT) is controversial, with conflicting results. This study addresses whether the convention for keeping atrioventricular (AV) delay constant during VV optimization might explain these conflicts. Method and results: Twenty-two patients in sinus rhythm with existing CRT underwent VV optimization using non-invasive systolic blood pressure. Interventricular optimization was performed with four methods for keeping the AV delay constant: (i) atrium and left ventricle delay kept constant, (ii) atrium and right ventricle delay kept constant, (iii) time to the first-activated ventricle kept constant, and (iv) time to the second-activated ventricle kept constant. In 11 patients this was performed with AV delay of 120 ms, and in 11 at AV optimum. At AV 120 ms, time to the first ventricular lead (left or right) was the overwhelming determinant of haemodynamics (13.75 mmHg at ±80 ms, P < 0.001) with no significant effect of time to second lead (0.47 mmHg, P = 0.50), P < 0.001 for difference. At AV optimum, time to first ventricular lead again had a larger effect (5.03 mmHg, P < 0.001) than time to second (2.92 mmHg, P = 0.001), P = 0.02 for difference. Conclusion: Time to first ventricular activation is the overwhelming determinant of circulatory function, regardless of whether this is the left or right ventricular lead. If this is kept constant, the effect of changing time to the second ventricle is small or nil, and is not beneficial. In practice, it may be advisable to leave VV delay at zero. Specifying how AV delay is kept fixed might make future VV delay research more enlightening.